2016
DOI: 10.1186/s12883-016-0735-8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in multiple sclerosis and associations with demographic, disease and lifestyle characteristics: an international cross-sectional study

Abstract: BackgroundSexual dysfunction (SD) is very common in people with multiple sclerosis (PwMS) and contributes a significant burden of disease, particularly for young people. SD has direct neurological contributions from depression and fatigue, which occur commonly in PwMS. Modifiable factors may represent potential targets for treatment and prevention of SD. We aimed to assess the prevalence of SD and explore associations between SD and demographic and modifiable risk factors, as well as depression and fatigue in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
49
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 45 publications
15
49
2
2
Order By: Relevance
“…Our study was designed to investigate prevalence and distribution of SD dimensions, and to identify contributory factors for SD in women with MS. The present findings support the results of previous studies, which have shown a high prevalence for sexual dysfunction among women with MS. [1,5,7,32,33]. In a systematic Meta analytic review in Iran (2019), the prevalence of SD was reported as 62% in [34] and as 34 to 85% in a review study in Canada (2014) [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was designed to investigate prevalence and distribution of SD dimensions, and to identify contributory factors for SD in women with MS. The present findings support the results of previous studies, which have shown a high prevalence for sexual dysfunction among women with MS. [1,5,7,32,33]. In a systematic Meta analytic review in Iran (2019), the prevalence of SD was reported as 62% in [34] and as 34 to 85% in a review study in Canada (2014) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Most MS patients (even those with mild degrees of disability) experience various sexual disorders that affect different aspects of their life significantly, which demonstrates the importance of the early identification and treatment of these disorders [4]. Sexual dysfunction due to MS is more prevalent in women than men, varying from 40 to 80% [5]. Many studies, including ones by Ghajarzadeh (2013), Merghati Khoei (2013) and Mohammadi (2008), have reported the prevalence of SD in Iranian women with MS as 66, 87.1 and 55.3%, respectively [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have various results and there is no overall estimate of the prevalence of sexual dysfunction in these patients. Given the high prevalence of this disease in Iran, its higher prevalence in women than in men, as well as the impact of sexual dysfunction due to this disease on women's quality of life (16), being aware of the exact level of the prevalence of sexual dysfunction in these patients can help physicians and health planners for design appropriate interventions and treatments.…”
Section: One Of the Most Important Complications Of This Dis-mentioning
confidence: 99%
“…Secondary sexual dysfunction is followed by MSrelated problems (such as bladder dysfunction). Tertiary sexual dysfunction occurs under psychosocial effects such as poor body image or low self-esteem [9].…”
Section: Sexual Disordersmentioning
confidence: 99%